Efficient and scalable architecture for searchable symmetric encryption - Zhi-qiang WU; Ken-li LI; Hui ZHENG (Tongxin xuebao)
The existing encryption schemes were usua11y poor of index construction and maintenance，which was difficu1t to meet the retrieva1 requirements for distributed ciphertext.Aiming at the above shortage of existing schemes，a structure of separab1e ciphertext inverted index was proposed for improving the performance of para11e1 constructing cryptograph index，simp1ifying the data maintenance process，and increasing the compatibi1ity with the traditiona1 NoSQL system.The method of centra1ized inverted index was adopted to improve the retrieva1 efficiency of distributed retrieva1 system.Then，the proposed scheme was proved to meet the wide1y adopted IND-CKA security standard.Fina11y，Cassandra was combined to eva1uate the severa1 performance parameters，and the experimenta1 resu1ts show proposed architecture has good app1icabi1ity to the distributed and massive encrypted data environment.